PENGARUH TENAGA KERJA DAN MODAL TERHADAP PENDAPATAN KELOMPOK WAITA TANI (STUDI KASUS USAHA DENDENG JANTUNG PISANG DI KORONG KP. TANGAH KENAGARIAN LURAH AMPALU KAB. PADANG PARIAMAN) - Cici Kumala Sari; Septria Susanti (BORJUIS: JURNAL OF ECONOMY, 2025)
The aim of this research is to analyze the influence of labor and capital on the income of a group of women farmers (case study of the banana blossom jerky business in Korong Kp. Tangah Kenagarian, Head of Ampalu District, Padang Pariaman District). This research is quantitative research, with data analysis techniques using statistical formulas, interview tools, observation and questionnaires. There were 30 respondents and data was collected through distributing questionnaires and documents obtained directly from the head of the women's farmer group. Using saturated samples taken from all members of the women farming group. This study's R-squared value of 59% indicates that capital and labour both influence income at the same time. In other words, 59% of the income-influencing factors are labour and capital. Furthermore, additional factors that were not included in this study account for 41% of the variation. The t test revealed that the women farmers' income was positively and significantly impacted by labour and capital. Government policymakers can utilize this information as a basis for choices about revenue growth, particularly in areas where regional development is a priority